Strategic management lessons from surah al-Kahfi - Mhd. Sarif, Suhaimi (Zes Rokman Resources, 2016)
Surah al-Kahfi contains essential contents related to the past, current and future direction of life as commented by many commentaries (tafsir). Since the contents are strategic, then motivates this study to examine strategic management lessons from Surah al-Kahfi. Strategic Management is a capstone subject in Business Management studies comprised various functional knowledge which include management, marketing, operations management, quality management, behavioural sciences, and social sciences. The lessons from Surah al-Kahfi could provide Tawhidic paradigm input into the studies. The study uses content analysis on the central themes in Surah al-Kahfi as highlighted by commentaries (tafsir) of the Qur’an. The study finds that integrating Quranic lessons into contemporary studies harmonizes the revelation (naqli) with the reasoning (aqli). Believers are firmly hold the Quran as source of guidance. Any physical and scientific evidence reinforces the contents in Quran. Nevertheless, believing in the revelation is partly the faith of Islam. The study suggests the lessons derived from Surah al Kahfi to be operationalize into the contemporary intellectual and practical contexts.